2019
DOI: 10.1001/jamanetworkopen.2019.3545
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a New Frailty Index for Older Surgical Patients With Cancer

Abstract: Key Points Question Can a more clinically feasible version of the modified Frailty Index for older patients with cancer be developed? Findings In this cohort study of 1137 older patients with cancer, the Memorial Sloan Kettering–Frailty Index (MSK-FI) was associated with aging-related impairments. A higher score on the MSK-FI was also associated with a longer length of stay, higher odds of intensive care unit admission, and lower overall survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 29 publications
2
57
0
Order By: Relevance
“…The development of the MSK-FI has been described elsewhere. 17 In brief, the MSK-FI was developed at Memorial Sloan Kettering on the basis of International Classification of Diseases, Ninth Revision ( ICD-9 ) 29 or International Statistical Classification of Diseases, Tenth Revision (ICD-10) 30 codes and includes 10 comorbid conditions and 1 item related to impairment of the 5 activities of daily living. 18 Scores for the MSK-FI range from 0 to 11, with higher scores indicating more frailty.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the MSK-FI has been described elsewhere. 17 In brief, the MSK-FI was developed at Memorial Sloan Kettering on the basis of International Classification of Diseases, Ninth Revision ( ICD-9 ) 29 or International Statistical Classification of Diseases, Tenth Revision (ICD-10) 30 codes and includes 10 comorbid conditions and 1 item related to impairment of the 5 activities of daily living. 18 Scores for the MSK-FI range from 0 to 11, with higher scores indicating more frailty.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that the MSK-FI is associated with the previously validated geriatric assessment and with postoperative outcomes of older patients with cancer. 17 Preoperative albumin level was measured in specimens drawn within 30 days before surgical treatment. We report adjusted 90-day mortality with corresponding 95% CIs around the difference in rates for the 2 groups.…”
Section: Methodsmentioning
confidence: 99%
“…The last clinical factor that emerged from our study was the association with neoplastic conditions: our study suggested a longer LOS for these patients. The associated frailty and possible extra needs of these patients as suggested by Shahrokni et al, should be taken into account and assessed with specific tools [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The unreimbursed cost to the family and time spent needs to be recognized. Because of much of geriatric assessment a self-administered we need to be creative in using information technology to accumulate and analyze the data that is needed to make interventions and to allow us to assess outcomes appropriately [8][9][10]. And of course, health care providers need additional time to take care of these patients with her complex issues.…”
mentioning
confidence: 99%